Studying Islam in the Arab World: The Rupture Between Religion and the Social Sciences - Hamed, Kante (Universitas Islam Internasional Indonesia, 2025)
Education plays a central and pivotal role in the fabric of societies and is a crucial aspect of human development. Governments, scholars, and institutions have long worked to enhance systems that deliver both meaningful knowledge to learners and effective ethical guidance. This issue is particularly relevant in the Arab and Islamic world, where traditional Shariah colleges and Islamic education curricula have historically been foundational but often stagnant. These systems have increasingly faced criticism for failing to address contemporary realities effectively.